LAYANAN PENGUASAAN KONTEN DENGAN TEKNIK MIND MAPPING DALAM MANUMBUHKAN MOTIVASI BELAJAR SISWA SEKOLAH MENENGAH PERTAMA - Perkasa, Maulid Dio; Wardani, Shabrina Indah; Masithoh, Agraita; Rahmi, Hadist Mutiara; Latif, Paramita Nur (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2025)
Low learning motivation among junior high school students often becomes an obstacle to achieving optimal academic outcomes. One strategic approach to addressing this issue is content mastery services within guidance and counseling, particularly through the application of the mind mapping technique. This technique helps students organize information, understand concepts visually, and increase their engagement with learning materials. This study employs a literature review approach by analyzing relevant previous research findings. The results indicate that the use of mind mapping not only enhances students’ comprehension and memory but also contributes to building motivation, improving learning mood, and facilitating time management in the learning process. Therefore, content mastery services using the mind mapping technique serve as an innovative solution to enhance students’ motivation and learning effectiveness at the junior high school level.